ANALISIS KECERDASAN SPIRITUAL ANAK USIA 5-6 TAHUN DI TK ISLAM AKRAMUNNAS KOTA PEKANBARU - Erma Sumiati; Ria Novianti; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstact :this study aims to analyze the spiritual intelligence of children aged 5-6 years in the Akramunnas Islamic City On Pekanbaru. The population is all children aged 5-6 years in the Akramunnas Islamic City On Pekanbaru 96 children. The sample of this study was 30 children. This type of research is decrictif qualitative. The data collection technique used is the observation sheet. The data collection tecnique used in this study is random sampling. Data analysis tecniques used the percentage formula, to the find the number of spiritual intellegence scores with 5 indicator, namely memorizing a few short suras, memorizing prayer movements perfectly, being able to mention some attributes of god, resoecting parents respecting friends, and loving his younger siblings or children in under his age, give thanks and thank you. The percentage of spiritual intelligence of children aged 5-6 years in the Akramunnas Islamic City Pekanbaru was 67,75% in the high category.Key Words: Spiritual intelligence